Pattern of Acute Pediatric Poisonings in Birjand City, East of Iran - Mehrpour, O; Sharifi, MD; Ebrahimi, M (International Journal of Medical Toxicology and Forensic Medicine, 2015)
Background: Acute pediatric poisoning represents a frequent cause of admission to the emergency departments. This descriptive and retrospective study was conducted in Birjand, eastern Iran, with the aim of evaluating the pattern of pediatric poisoning in this region. Methods: During the 6-year period from 21st March 2006 to 20th March 2012, all files of pediatrics poisoned patients admitted to the emergency department of Vali Asr teaching hospital was reviewed and the data were recorded in a pre-designed form. The results were analyzed by relevant statistical tests. Results: During this period, 246 cases (41.1% female and 58.9% male) were admitted with a diagnosis of acute poisoning. The mean age was 37.6 +/-32.64 (range: 0.06-156) months. The majority of poisonings occurred in the children aged about 2 to 5 years. The most common agents involved were opioids (39.43%), pharmaceuticals (22.76%) and envenomations (15.9%). Most of the patients were living in urban areas (56.91%). There was a significant correlation between older age and intentional poisoning (P<0.01). There were also significant correlations between the toxic agent and either the season (P<0.0001), or patients’ age (P<0.0001), residential status (P=0.008) and or consciousness (P<0.0001). Moreover, we introduced Majoon Birjandi as a new cause of poisoning in the literature. Conclusion: Acute opium poisoning was the most common in terms of morbidity and mortality in this region. Health authorities should consider preventive programs in this regard. Moreover, Majoon-e-Birjandi as a new cause of poisoning should be considered in this region, which is not previously reported in the literature.